RESULTS OF INDUSTRIAL WATER TREATMENT FROM MECHANICAL IMPURITIES - Khurmamatov, Abdugaffor; Boyturayev, Sarvar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The paper presents the results of separation of mechanical impurities of technical waters. With the help of the proposed effective technology and with the use of an improved filter, it is possible to purify technical water up to 0.03%. As a result of improvement of the device for purification of technical water from mechanical impurities the following positive results are obtained: a new effective technology of purification of technical water from mechanical impurities is developed; due to improvement of the device for separation of mechanical impurities from the composition of technical water the productivity of the device is increased from 35 m3/s to 45 m3/s.